The Role of Accounting Information Systems And Technology Innovation on Financial Performance and Business Risks of Msmes - Yeni Triyana; David Pangaribuan; Wahid Ansori (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Accounting Information Systems (AIS) play a crucial role in managing corporate finances, improving the efficiency, accuracy, and transparency of transaction recording and financial reporting. They help management make informed decisions. The use of information technology helps identify potential risks early, monitor conditions in real time, and respond more quickly and precisely. Business risks faced by SMEs include financial and operational risks, reducing the risk of human error, strengthening accountability, and improving internal controls, thus minimizing misuse of funds. The application of technology has a positive impact on SMEs, increasing operational efficiency and competitiveness. SMEs support sales transactions, promotional media, and simplify transaction data storage, build business relationships, and control business operations. These can be done anywhere, regardless of time and space